The Influence of Cross-Interest Learning in Economics Subjects on the Growth Of Students' Entrepreneurial Interest at SMAN 11 Pangkep - Husain; Muh. Yahya; Devilla, Rego (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
In the current era, learners must have the ability to be able to adapt to changes that occur in the education component. One of these demolitions is in the 2013 curriculum in which there are specialization subjects. This study aims to find out how the influence of cross-interest learning in economics students on the growth of entrepreneurial interest of SMAN 11 Pangkep students. This research is a type of descriptive quantitative research. The population and sample of this study are grade XI science students totaling 26 students for the 2021/2022 academic year. Data collection techniques are carried out by distributing questionnaires and documentation. Analysis techniques use descriptive statistics and inferential statistical analysis. The results showed that there was a significant influence of cross-interest learning (X) on the growth of entrepreneurial interest (Y) in grade VI IPA students of SMA Negeri 11 Pangkep, where a probability value of 0.04 < 0.05 was obtained and a calculated t value of 2.122 > 1.714. Thus, it is concluded that cross-interest learning of economics subjects needs efforts made by principals and teachers so as to be able to increase the growth of students' entrepreneurial interest after graduation considering the importance of entrepreneurial spirit in this country.